Menjadi Muslim di Freiburg: Studi Kasus Praktik Keagamaan Komunitas Muslim di Freiburg, Jerman - Tuti Elfrida (Jurnal Kajian Wilayah, 2013)
There are many studies focus on minority cases that done by many researchers or scholars. But most of studies correlate minority group with the discrimination issues, human right, freedom, or the relation toward majority group and state. This study, then, provides another side of minority life of Moslem in Freiburg, Germany. Specifically, this study is explaining the religious practice of Moslem in Freiburg and asking on how do Moslems practice their religion in Freiburg individually,how does the Moslems daily life in Freiburg regarding the religious practice, and how does the Moslem organizations role for the existence of the Islam religious practice in Freiburg. To gain data, this research uses qualitative method through observation, participant observation, and interview. From this research, well know that every Moslem has their own ways to practice their religion.They still associate themselves toward the community or organization based on ethnic or nationality, including practicing religious rituals. Some of informants are still identifying themselves as Turkish, Palestinian, Arabic, Algerian, or other nationality not as Freiburger. In addition, there are some changes regarding Islamic religious practice. They also do not always require the provision of facilities, but tend to adapt for their religious practice. In their daily interaction, not all of the informants are interacting with their non-Moslem friends. The level of religiosity also affect their social interaction and ways to practice religion. However, they are still trying to achieve the balance of life, both as Moslem and Freiburger.Key words: Moslem community, religious practice, ethnic boundary, interaction, adaptation.